Shedding Light onto the City Blues Myth—The Potential of Stimulating and Activating Effects of Urban Public Spaces and the Role of City Relatedness - Lämmle, Lena; von Lindern, Eike; Rummel, Dorothee; Michaeli, Mark; Ziegler, Matthias (International journal of environmental research and public health, 2022)
The present study aims to investigate whether a sense of relatedness to a city helps to broaden understanding of the restorative potential of urban public spaces. Findings based on a sample of German adults (n = 249) confirm that people experience relatedness to a city. The study’s 3 × 3 (built, mixed, natural environment) × (average, livability environment, bird’s-eye view) design revealed disordinal interactions for being away, fascination, preference, mental fatigue, and stimulating and activating effects associated with cities. This implies that humans’ place perceptions are more complex than previously assumed. Both city and nature relatedness were relevant covariates of these findings. Surprisingly, the construct ‘activating effects’, was found to be mostly perceived as more positive for mixed and built environments compared to natural environments. Thus, complementing restorative environments research by introducing a measure for city relatedness significantly enhances understanding of the potential of urban public spaces for promoting human health and well-being.